High assurance on cyber-physical interactive systems - Couto, Rui (2019)
Cyber-Physical Systems, as distributed systems of computational elements interacting with the physical world, are highly complex systems. They can, in many instances, be considered safety critical interactive systems, as errors in interaction can have disastrous consequences (consider the case of autonomous vehicles or integrated clinical environments). High assurance is, then, an underlying requirement, also at their user interface. In this position paper we identify five challenges to be solved both in the short and in the long term, regarding the modelling of (1) distributed and (2) heterogeneous interactive systems, (3) the analysis and relation between the different abstraction layers of Cyber-Physical Systems, (4) the modelling of real time/hybrid systems, and (5) the modelling of the dynamic nature of such systems. Solutions for these challenges are not presented, but possible directions are discussed.